2020
DOI: 10.1099/jmm.0.001222
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multi-center evaluation on risk factors, clinical characteristics and outcomes due to carbapenem resistance in Acinetobacter baumannii complex bacteraemia: experience from the Chinese Antimicrobial Resistance Surveillance of Nosocomial Infections (CARES) Network

Abstract: Introduction. Increasing evidence demonstrates unfavourable outcomes in bloodstream infections (BSI) due to the carbapenemresistant Acinetobacter baumannii complex (CRAB).Aim. To investigate the differences in risk factors, clinical characteristics and outcomes in patients with A. baumannii complex BSI stratified by carbapenem resistance, a prospective multi-center study was conducted.Methodology. Information was collected in a predefined form. A total of 317 cases was included for comparison between CRAB BSI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…Risk factors for the acquisition of CRAB include endotracheal intubation and carbapenem use [ 8 , 9 ]. All patients in our outbreak were mechanically ventilated, but none were exposed to carbapenems before acquisition of CRAB.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for the acquisition of CRAB include endotracheal intubation and carbapenem use [ 8 , 9 ]. All patients in our outbreak were mechanically ventilated, but none were exposed to carbapenems before acquisition of CRAB.…”
Section: Discussionmentioning
confidence: 99%
“…This study was an investigative and predictive analysis based on BSI patients' clinical data from the CARES study (Chinese Antimicrobial Resistance Surveillance of Nosocomial Infections), which is a nationwide, longitudinal, prospective study encompassing 16 tertiary-care teaching hospitals in 10 provinces in China between 2007 and 2016 (15)(16)(17). Each hospital has at least 1,200 beds and one infectious disease department and infection control committee with specialist doctors, nurses, and microbiological laboratory personnel.…”
Section: Methodsmentioning
confidence: 99%
“…Investigating the pattern of pathogens in the ICU environment, especially for MDR organisms, will help develop specific prevention and control strategies. A recent study in a tertiary teaching hospital in western China reported that Acinetobacter baumannii was the leading cause of infection in almost every ICU (7). In this study, ESBL-E was the most prevalent pathogen in ICU non-adult patients in Zhejiang Province (43.4% to 53.8%).…”
Section: Discussionmentioning
confidence: 56%